Overview of Tuberculosis Knowledge among SMK Telkom Malang Students - R Sugiri, Yani Jane; Tantular, Rezki; Binharyanto, Adlan Pratama; Pratiwi, Eka; Muhammad, Iqbal; Asyari, Claudia Herda; Dini, Zata; Primaputri, Cindy Carissa; Lyono, Albert; Susanti, Lia; Delfianto, Dwiroza; Aprilen, Nisa; Suardana, I Made; Murti Dewi, Dian Ayu; Wikamto, Rifka (Fakultas Kedokteran Universitas Brawijaya, 2025)
Tuberculosis has emerged as a major global health challenge. Public knowledge about TB is crucial for its prevention, early detection, and management. Research conducted by the World Health Organization indicates that a good level of knowledge about Tuberculosis among the public can significantly enhance symptom recognition, timely medical care, and reduce the stigma. This study aims to describe the TB knowledge of SMK Telkom Malang students. A quasi-experimental pretest-posttest design was conducted involving 415 students, of whom 336 completed both assessments. TB knowledge was measured using a 10-item validated questionnaire and categorised as good, sufficient, or poor. The Wilcoxon signed-rank test was used for statistical analysis. They were then given health education about TB, after receiving health education about TB, 69 students did not consent to continue the study or complete the posttest and were therefore excluded, leaving 336 students as sample. Pretest demonstrated 225 students (67%) with good knowledge, 93 students (27,7%) with sufficient knowledge, and 18 students (5,3%) with poor knowledge, the overall median was 80, while posttest analysis revealed 264 students (78.6%) with good knowledge, 66 students (19.6%) with sufficient knowledge, and 6 students (1,8%) with poor knowledge, the overall median was 90 . The scores were compared using the Wilcoxon test with significantly improved score with a p-value of <0.001. In conclusion, health education significantly improved TB knowledge among students. Continued efforts to integrate TB education in schools are recommended to support TB control strategies.